Cyclic homodimer formation by singlet oxygen-mediated oxidation of carnosine - Kawakami, Hiroko; Itakura, Yuki; Yamamoto, Tetsuya; Yoshiya, Taku (Frontiers in Chemistry, 2024)
Although carnosine (β-Ala-L-His) is one of physiological protectants against in vivo damages caused by reactive oxygen species (ROS), its reactivity against singlet oxygen ( 1 O2), an ROS, is still unclear at the molecular level. Theoretically, the reaction consists of two steps: i) oxygenation of the His side chain to form an electrophilic endoperoxide and ii) nucleophilic addition to the endoperoxide. In this study, the end product of 1 O2-mediated carnosine oxidation was evaluated using 2D-NMR and other analytical methods both in the presence and absence of external nucleophiles. Interestingly, as the end product without external nucleophile, a cyclic homodimer was confirmed under our particular conditions. The reaction was also replicated in pork specimens.